Take your seats: leftward asymmetry in classroom seating choice - Harms, Victoria L.; Poon, Lisa J. O.; Smith, Austen K.; Elias, Lorin J. (Frontiers in Human Neuroscience, 2015)
Despite an overall body symmetry, human behaviour is full of examples of asymmetry, from writing or gesturing to kissing and cradling. Prior research has revealed that theatre patrons show a bias towards sitting on the right side of a movie theatre. Two competing theories have attempted to explain this seating asymmetry: one posits that expectation of processing demand drives the bias; the other posits that basic motor asymmetries drive the bias. To test these theories we assessed the real-world classroom seating choices of university students using photographs. A bias for students to choose seats on the left side of the classroom was observed, in contrast to the right side bias observed in theatre seating studies. These results provide evidence in support of a processing-expectation bias.